2022
DOI: 10.3390/biomedicines10061446
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Microglia/Macrophage Activation by CDNF Promotes Transplantation of Fetal Ventral Mesencephalic Graft Survival and Function in a Hemiparkinsonian Rat Model

Abstract: Parkinson’s disease (PD) is characterized by the loss of dopaminergic neurons in substantia nigra pars compacta, which leads to the motor control deficits. Recently, cell transplantation is a cutting-edge technique for the therapy of PD. Nevertheless, one key bottleneck to realizing such potential is allogenic immune reaction of tissue grafts by recipients. Cerebral dopamine neurotrophic factor (CDNF) was shown to possess immune-modulatory properties that benefit neurodegenerative diseases. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Furthermore, in further studies, authors have indicated the involvement of CDNF in the reduction of LPS-induced inflammation through the competitive inhibition of Akt phosphorylation and suppression of downstream pathways, including forkhead box protein O1 (FoxO1) and mTOR signaling [ 105 ]. Another study showed that the modulation of inflammatory responses caused by CDNF is not only by decreasing microglia/macrophage recruitment but also regulating its polarization and enhancing M2 subset polarization [ 121 ]. Degeneration of dopaminergic neurons can be caused by several processes, among which the oligomerization of α-synuclein and the deposition of these forms of α-synuclein in the cytoplasm of neurons play a key role.…”
Section: Neurotrophic Factors In Glia-neuronal Crosstalk and Their Ro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in further studies, authors have indicated the involvement of CDNF in the reduction of LPS-induced inflammation through the competitive inhibition of Akt phosphorylation and suppression of downstream pathways, including forkhead box protein O1 (FoxO1) and mTOR signaling [ 105 ]. Another study showed that the modulation of inflammatory responses caused by CDNF is not only by decreasing microglia/macrophage recruitment but also regulating its polarization and enhancing M2 subset polarization [ 121 ]. Degeneration of dopaminergic neurons can be caused by several processes, among which the oligomerization of α-synuclein and the deposition of these forms of α-synuclein in the cytoplasm of neurons play a key role.…”
Section: Neurotrophic Factors In Glia-neuronal Crosstalk and Their Ro...mentioning
confidence: 99%
“…Based on the promising results of animal studies [ 64 , 101 , 109 , 113 , 121 , 131 ], it was hypothesized that NTFs could be a potential regenerative tool in inflammatory and degenerative conditions of the CNS. Each NFT has its unique profile of action on specific subsets of neurons to ensure their optimal function.…”
Section: Conclusion and Further Prospectsmentioning
confidence: 99%
“…Inflammatory cytokines produced by activated microglia participate in the progression of PD pathogenesis (154). Increasing evidence suggests that CDNF and MANF possess immunomodulatory functions that contribute to their cytoprotective and neuroprotective properties (56,88,94,111,155). Although MANF was originally isolated as a secreted factor from the culture medium of a mesencephalic astrocyte cell line (18), it was noted that in normal conditions MANF expression is low in brain glial cells but can be induced upon glial cell activation in stress conditions (156).…”
Section: Manf and Cdnf In Inflammationmentioning
confidence: 99%
“…Therapeutic efficacy of CDNF may depend on several factors such as the severity of PD model and the route of administration. After injections of 6-OHDA into the MFB, CDNF has not achieved neuronal restoration in rodent PD models ( 111 , 112 ). CDNF could improve only apomorphine-induced rotational asymmetry ( 112 ).…”
Section: Cdnf Manf and In Vivo Pd Modelsmentioning
confidence: 99%
See 1 more Smart Citation